Critical Thinking Skills of Elementary School Students Through an Inductive Thinking Learning Model on Animal Breeding Lessons - Nurdiansyah, Deni; Ependi, Utep Herlina; Setiawan, Dede (PrimaryEdu : Journal of Primary Education, 2023)
This research is motivated by the tendency of low critical thinking skills of elementary school students. The habit of memorizing and remembering material in books is one of the factors that influence it. This study aims to determine the critical thinking skills of elementary school students at each stage of the inductive thinking learning model. The method used in this study is a qualitative descriptive method. The research participants involved 7 grade VI students in one of the public elementary schools in Cipongkor District, West Bandung Regency on animal breeding material. The instruments used in data collection were observation sheets and test questions. The research data were analyzed qualitatively through scoring and percentages based on the emergence of aspects of critical thinking indicators. The results showed that the average percentage of students' critical thinking skills indicators in the high category based on the results of the observation of the syntax of the inductive thinking learning model was 65,6%, and 67% based on the results of the description test. Thus, the researcher can conclude that the implementation of the inductive thinking learning model is effectively used to improve the critical thinking skills of elementary school students.